2017
DOI: 10.1111/apt.14429
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of sofosbuvir‐based treatment of acute hepatitis C in end‐stage renal disease patients undergoing haemodialysis

Abstract: A half dose of sofosbuvir (200 mg once daily) plus a full dose of daclatasvir (60 mg once daily) were suitable for the treatment of acute HCV-infected patients who were undergoing end-stage renal disease and were on haemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
(25 reference statements)
1
18
0
Order By: Relevance
“…In our study, all patients were treated with full-dose SOF-based regimen for 12 weeks and they demonstrated excellent SVR12. The previously reported data and our data suggested that the dose of SOF could be an important variable to reach SVR in HD patients and that a reduced dose might lead to sub-therapeutic exposure and the risk of treatment failure [15,17]. Therefore, full-dose SOF regimen might be more effective to reach SVR in HD patients.…”
Section: Discussionsupporting
confidence: 50%
“…In our study, all patients were treated with full-dose SOF-based regimen for 12 weeks and they demonstrated excellent SVR12. The previously reported data and our data suggested that the dose of SOF could be an important variable to reach SVR in HD patients and that a reduced dose might lead to sub-therapeutic exposure and the risk of treatment failure [15,17]. Therefore, full-dose SOF regimen might be more effective to reach SVR in HD patients.…”
Section: Discussionsupporting
confidence: 50%
“…The included studies were published from 2015 to 2020 and contained extractable data on 514 patients enrolled from 2014 to 2016. Four studies were retrospective [10][11][12][13] and 16 were prospective [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Nine of the studies were conducted in India 10,12,14,16,18,20,22,25,29 , 2 in the USA 15,21 , 2 in Pakistan 24,28 , 2 in China 19,27 , 1 in France 17 , the Czech Republic 11 , Korea 13 , Iraq 26 , and 1 enrolled patients from multiple countries 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Since this drug is eliminated by renal pathway, its use in patients with renal impairment raised the concerns of drug accumulation. Among the included studies in this meta-analysis, the majority used a standard dosing, that is, 400 mg per day, and only two studies 23,30 used half-dose sofosbuvir, which also achieved satisfactory SVR12 rates. A reduced dose of sofosbuvir might help to alleviate the risk of further renal impairment, however, well-designed comparison studies of standard and reduced dosing are needed to further elucidate the efficacy and safety profile of sofosbuvir at reduced dose.…”
Section: Discussionmentioning
confidence: 99%